Unraveling neurovascular mysteries: the role of endothelial glycocalyx dysfunction in Alzheimer’s disease pathogenesis - O’Hare, Nicholas; Millican, Karina; Ebong, Eno E. (Frontiers in Physiology, 2024)
While cardiovascular disease, cancer, and human immunodeficiency virus (HIV) mortality rates have decreased over the past 20 years, Alzheimer's Disease (AD) deaths have risen by 145% since 2010. Despite significant research efforts, effective AD treatments remain elusive due to a poorly defined etiology and difficulty in targeting events that occur too downstream of disease onset. In hopes of elucidating alternative treatment pathways, now, AD is commonly being more broadly defined not only as a neurological disorder but also as a progression of a variety of cerebrovascular pathologies highlighted by the breakdown of the blood-brain barrier. The endothelial glycocalyx (GCX), which is an essential regulator of vascular physiology, plays a crucial role in the function of the neurovascular system, acting as an essential vascular mechanotransducer to facilitate ultimate blood-brain homeostasis. Shedding of the cerebrovascular GCX could be an early indication of neurovascular dysfunction and may subsequently progress neurodegenerative diseases like AD. Recent advances in in vitro modeling, gene/protein silencing, and imaging techniques offer new avenues of scrutinizing the GCX's effects on AD-related neurovascular pathology. Initial studies indicate GCX degradation in AD and other neurodegenerative diseases and have begun to demonstrate a possible link to GCX loss and cerebrovascular dysfunction. This review will scrutinize the GCX's contribution to known vascular etiologies of AD and propose future work aimed at continuing to uncover the relationship between GCX dysfunction and eventual AD-associated neurological deterioration.